Sustainable development in amenity-based communities of the Greater Yellowstone Ecosystem - Bergstrom, Ryan Dennis (Kansas State University, 2012)
The Greater Yellowstone Ecosystem (GYE) is a large, nearly intact ecosystem with significant protection that has often been considered an ideal location to examine coupled human-environment interactions due to the region’s complex mosaic of private and public lands, competing natural resource uses, and rapid population growth. A transition toward sustainability suggests that current societal and economic needs can be met while simultaneously maintaining the planet’s life support systems for future generations. To facilitate sustainability transitions it is imperative that the perceptions and experiences of local communities be documented. The objective of this study was to determine how residents of amenity-driven gateway communities (West Yellowstone and Red Lodge, Montana, and Jackson, Wyoming) surrounding Yellowstone and Grand Teton national parks perceive and experience their transition toward sustainability and the challenges inherent in that transition, how those perceptions inform locally produced and extra-local policies, and how institutions influence sustainability goals. Further, this study determined which factors contribute to these perceptions, and whether they differed spatially and temporally. To meet study objectives, a mixed methods approach was implemented, including the content analysis of local newspapers and key informant interviews. Content analysis of local newspapers was used to investigate decision maker and stakeholder priorities for the local and regional environment, economy, and communities, and to determine what actions had been taken to promote sustainability. A total of 193 articles from West Yellowstone News, 287 articles from Carbon County News, and 333 articles from Jackson Hole News & Guide for the ten year period 2000-2009, were analyzed. Specific focal topics varied among the newspapers/communities, but in general terms the most discussed topics in West Yellowstone during this time were focused on natural resources, economic development, community development, sustainability and conservation, and growth and development. The most discussed topics for Red Lodge were community development, government services, tourism and recreation, and growth and development. The most commonly discussed topics in Jackson were natural resources, growth and development, community development, and government services. A total of 35 semi-structured interviews were conducted with key informants in the three study communities during the summer of 2010 to allow for specific questioning and to gain additional information. Definitions of sustainability differed based on the key informant’s community, role in the community, and length of residence in the community. Overall, definitions of sustainability focused on the environment, the economy, and multi-generational or long-term thinking. The prioritization of the economy, environment, and society also differed based on community; however, there was overall recognition that each community was dependent upon the natural environment for economic vitality. In all three study communities, dependence on tourism and recreation-based industries, the lack of a diversified economy, and continued growth and development have resulted in a disconnect between perceptions, priorities, and goals as they relate to sustainability. In addition, each community was focused on multiple goals that further complicated the fulfillment of sustainability objectives. The multi-goal orientation of study communities is reflected in the multiple visions that various decision makers and stakeholders have for the community and their futures. What is needed most is a hierarchical approach to a sustainability transition, with each community setting its own, as well as ecosystem-wide, goals, objectives, and visions. Findings suggest that a transition toward sustainability is perceived and experienced differently based on local context. In the GYE, that context includes a tourism-based economy that is dependent upon the natural environment, a myriad of local, regional, national, and global stakeholders, and the presence of federal land agencies that are responsible for the sustainability of natural systems, freeing local communities to focus on the societal and economic dimensions of sustainability. A transition toward sustainability will be manifested differently in the Greater Yellowstone Ecosystem, and potentially other communities adjacent to protected lands, than it is other areas because of its unique milieu. While the close proximity of federal lands, including Yellowstone National Park, may complicate the sustainability discourse at times and may, in certain instances, add additional challenges through extra-local control of change, these same federal lands may also favor a transition toward sustainability in amenity-driven gateway communities. In addition, the disparate socio-economic conditions present in study communities, as well as extra-local institutions and agencies, directly influence, and may at times further complicate, a transition toward sustainability. This study is based on the theory that in order to successfully transition toward sustainability, a better understanding of coupled human and natural systems is critical, and because of the close couplings between human and natural systems in the Greater Yellowstone Ecosystem, and because of the unique challenges and conflicts present in the region, the GYE is an ideal location to study human-environment interactions. The use-inspired orientation of sustainability science aims to provide tangible, real-world, and place-based understanding of a transition toward sustainability. The contribution of this study to the field of sustainability science is the understanding that, while sustainability visions, goals, and objectives may be similar across a region, consideration of local contexts affecting goals and perceptions provides valuable insights that may inform sustainability pathways at local scales and, as a result, provide deeper understanding of global sustainability. One of these insights is that communities that seemingly have much in common due to their shared region, physical environmental surroundings, and history, the specific concerns to ensure place-based sustainability can show variability. Another important point from this research is that, while most depictions of sustainability are focused on three elements—the economy, society, and the environment—individuals also key in on multigenerational concerns.
Keywords: Sustainability; Greater Yellowstone Ecosystem; Human-environment interaction; Geography (0366)